2007
DOI: 10.1111/j.1365-2109.2007.01768.x
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of silver barb Puntius gonionotus (Bleeker) with Indian major carps in a grow-out polyculture

Abstract: The compatibility and growth performance of silver barb Puntius gonionotus (Barbonymous gonionotus) with the three Indian major carps, i.e., Catla catla, Labeo rohita and Cirrhinus mrigala, were assessed in a 10-month carp polyculture trial. Treatments T-1, T-2, T-3 and T-4 were stocked with three of the above four carp species, with an absence of silver barb, mrigal, rohu and catla, respectively, while all four species were stocked in treatment T-5. The treatments were stocked at 6000 ¢ngerlings ha À1 , with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 6 publications
0
16
1
Order By: Relevance
“…The total ammonia‐nitrogen (TAN) and nitrate‐nitrogen ranged from 0.12 to 0.93 mg L −1 and 0.18 to 0.8 mg L −1 respectively. In general, both TAN and nitrate showed an increasing trend with the advancement of rearing period, attributed to the gradual accumulation of metabolites and dissolved organic matter from faeces, leftover feed and dead plankton (Jena, Das, Mondal & Das ; Jena, Das, Kar & Singh ).…”
Section: Resultsmentioning
confidence: 99%
“…The total ammonia‐nitrogen (TAN) and nitrate‐nitrogen ranged from 0.12 to 0.93 mg L −1 and 0.18 to 0.8 mg L −1 respectively. In general, both TAN and nitrate showed an increasing trend with the advancement of rearing period, attributed to the gradual accumulation of metabolites and dissolved organic matter from faeces, leftover feed and dead plankton (Jena, Das, Mondal & Das ; Jena, Das, Kar & Singh ).…”
Section: Resultsmentioning
confidence: 99%
“…After the sixth‐month harvest (second phase), the density of the three IMC were more or less similar in control, T‐1 and T‐3 and higher in T‐2. But by this time, the IMCs in T‐1 must have experienced greater interspecific competition from minor carps during the first phase of culture (Das & Mishra, ; Haque, Wahab, Wahid, & Haq, ; Jena et al, ; Jena, Das, Mondal, & Das, ). Similarly in T‐2, these species were exposed to greater intraspecific competition throughout the culture period (Das & Mishra, ; Mohanty, ) as their initial density as well as density after the partial harvest remained higher than the other treatments.…”
Section: Resultsmentioning
confidence: 99%
“…But in presence of MCB group in T2, T3 and T4, catla showed lower HBW indicating probable interference from silver barb, the other surface feeder in the system. Though Jena et al (2007) have reported compatibility of silver barb with catla, probably the observed aggressive feeding behaviour of the former towards floating pellet ensured its primary access to supplementary feed, there by affecting growth of the later in these treatments. In fact, silver barb exhibited almost comparable growth as that of catla in T2 and T3.…”
Section: Resultsmentioning
confidence: 99%
“…Attempts are made to diversify the major carp based composite culture systems by changing the composition incorporating minor carps. Minor carps such as kalbasu (Labeo calbasu Hamilton), fringe-lipped carp (Labeo fimbriatus Bloch), kuria labeo (Labeo gonius Hamilton), bata (Labeo bata Hamilton), reba (Cirrhinus reba Hamilton) and barbs such as silver barb (Puntius gonionotus Bleeker) and olive barb (Puntius sarana Hamilton) have shown promising results in terms of compatibility with major carps and possibility of increasing the biomass yield (Haque et al,1998;Sahu et al, 2007;Jena et al, 2007Jena et al, , 2008Jena and Das, 2011). Most of the studies, however, have been restricted to inclusion of one or two of these species in the major carp system at a time.…”
Section: Introductionmentioning
confidence: 99%